Upper extremity functions, social relationships, and factors associated with poor quality of life in patients with burns at kiruddu hospital - Osman, Kamaludin D.; Alenyo, Rose; Mbiine, Ronald; Murithi, Benard M.; Sheikdon, Abdirizak A. (International journal of burns and trauma, 2022)
Burn is the major cause of disability in developing countries, and most burn patients have burns involving the upper limbs. Upper limb burns can result in scarring, contractures, and weakness, leading to limitation of wide range of movements and social well-being, hence reducing the quality of life. General objective: To determine the quality of life among patients with burns of the upper limbs at KNRH. Methods: This cross-sectional study recruited 108 participants of 5 years and above during their first six months post-discharge from Kiruddu National Referral Hospital with burns to upper limbs. Recruitment was consecutive from the burns unit clinic following ethical approval from the School of Medicine Research and Ethics Committee (SOMREC). Participants were given a burn-related QOL questionnaire. Data were then entered into Epidata 4.2 and imported into STATA 15.1 for analysis. Factors associated with poor quality of life were determined by modified Poisson regression to generate prevalence ratios with 95% confidence intervals. Results: A total of 108 participants were recruited for the study; 97 (89.8%) were adults and responded to the adult QOL questionnaire, while the rest were pediatrics. The mean age of the adults was 28 years (SD=8.6), while the median age of the pediatrics was eight years (IQR=6-10), and 61.1% were male. The upper extremity function (physical) quality of life was good, while the social relationship quality of life was poor. The factors associated with poor quality of life were degree (deep) of burns, multiple surgeries, age above 55 years, and being divorced. Conclusions: There is generally poor upper extremity function or physical QOL among adults and children, while there is generally good social relationship QOL among adults and children.
Keywords: Upper extremity functions; Burns; Quality of life; Factors associated